A LEGAL ANALYSIS OF SURROGATE MOTHERS FROM THE PERSPECTIVE OF INDONESIAN CRIMINAL LAW - Sintia Siregar; Kiki Kristanto; Karlinae D. Bangas; Agus Mulyawan (RADJA PUBLIKA, 2026)
The practice of surrogacy is a solution for infertile couples, but it creates legal problems in Indonesia. This normative juridical research analyzes Indonesian criminal law regulations regarding the practice of surrogacy and the criminal liability of doctors involved. The results show that although Law Number 17 of 2023 concerning Health and Ministerial Regulation No. 2 of 2025 prohibit the practice of womb borrowing, these provisions only regulate administrative sanctions without clear criminal threats, thus creating a vacuum in criminal law norms. To anticipate this legal vacuum, the Law on the Eradication of the Crime of Human Trafficking and the Law on Child Protection can be implemented through legal interpretation. The criminal liability of doctors is based on the principle of personal liability through articles in the Criminal Code, as well as professional sanctions based on the Indonesian Code of Medical Ethics. This research concludes that Indonesia needs special regulations that integrate proportional criminal sanctions to provide legal certainty and protect all parties involved.